Diverse Habitat Types Support High Bird Diversity in Jali River Estuary, Purworejo, Central Java, Indonesia - Hendry Fauzy, Noorman; Yeni A. Mulyani; Ani Mardiastuti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2026)
The Jali River estuary a compact 5.45-hectare mosaic of nine habitat types on Java's south coast, was surveyed from March to May 2023 to assess its avian diversity and community structure. Using point counts (n=12 points, 3 replicates) conducted during low tide periods, we recorded 229 individual encounters representing 41 species from 19 families. The estuary exhibited high overall bird diversity (Shannon-Wiener H' = 3.212 ± 0.102) with moderate evenness (E' = 0.605). Standardized encounter rates varied across habitats, with the River and Pandanus stand showing the highest values. Analysis of community similarity (Bray-Curtis index) revealed five distinct ecological clusters, demonstrating that bird assemblage composition was driven more by habitat structure and resource availability than by spatial proximity. This was further supported by NMDS ordination (stress = 0.14) and SIMPER analysis, which identified key indicator species such as the Zitting Cisticola for open terrestrial clusters and the Cerulean Kingfisher for mangroves. The estuary's significant conservation value is highlighted by the presence of eight species protected under Indonesian law (PERMENLHK P.106/2018), including the globally Endangered Great Knot (Calidris tenuirostris) and the Vulnerable Christmas Frigatebird (Fregata andrewsi). These findings underscore that even small, heterogeneous estuaries can support high avian diversity and serve as vital refuges for threatened species, necessitating targeted conservation strategies focused on preserving critical habitats like mudflats, river corridors, and Casuarina stands.